Interference Analysis of Medium Voltage Air Line 20 KV Feeder Using Failure Mode and Effects Analysis Method - Yan Min Tun; Aung Than Win (Newinera Publisher, 2020)
This article discusses the interference analysis of medium voltage air line 20 kv feeder using failure mode and effects analysis method. The distribution network consists of two parts, the first the distribution network consists of two parts, the first is the medium / primary voltage (JTM) network, which supplies electrical power from the sub-transmission substation to the distribution substation, the primary distribution network uses three wires or four wires for three phases. the impact of the reliability index from the calculation of the impact of the reliability index based on the number of disturbances (SAIFI), it shows that in January 2019 it has the highest index value, namely SAIFI, 1,695 disturbances/ subscribers. From the results of the calculation of the impact of the reliability index based on the number of blackouts (SAIDI), it shows that in January 2019 the SAIDI index value was 3,883 hours/customer.